2019
DOI: 10.1002/aelm.201900768
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable, Solution‐Processed Ga‐Doped IZTO Thin Film Transistor by Ar/O2 Plasma Treatment

Abstract: their high optical transparency and high mobility. The undoped InO x and ZnO have a crystalline structure with high carrier concentration. [23] Therefore, many attempts are carried out to improve TFT performance by using multi-component metal-oxides. [24][25][26][27][28][29][30][31][32] IGZO is a widely used metal-oxide because of its amorphous structure and relatively high mobility. [8,32] The mixing of two or more cations with different sizes and ionic charges is tried for amorphous phase with suppressing cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…Small ∆V TH indicates fewer defects at the interface of the GI and the active layer. The negligible change in the SS after bias stress from 0 to 1 h indicates very small trapping sites at the interface [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Small ∆V TH indicates fewer defects at the interface of the GI and the active layer. The negligible change in the SS after bias stress from 0 to 1 h indicates very small trapping sites at the interface [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since Hosono's group proposed amorphous oxide semiconductors (AOS) like amorphous IGZO channel in 2004, various metal oxide semiconductor channels including indium zinc oxide (IZO), zinc tin oxide (ZTO), gallium tin oxide (GTO), indium zinc tin oxide (IZTO), zinc oxide (ZnO), and titanium oxide (TiO 2 ) have been reported as a promising channel material for TFTs to substitute Si channel. [1][2][3][4][5][6][7][8][9][10][11][12] Many groups have extensively investigated metal oxide channel materials for thin film transistors (TFTs) for the next generation flat panel displays. Due to the large band gap and high transmittance of typical AOSs, those oxide semiconductor channels could also previous reports have covered the effects of incorporation of stabilizing dopants on the device performance and stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the TFT performance, multi-component oxide semiconductors are of increasing interest, such as zirconium-indium-zinc oxide (ZIZO), aluminum-zinc-tin oxide (AZTO), amorphous indiumgallium-zinc oxide (a-IGZO), amorphous indium-zinc-tin oxide (a-IZTO), amorphous aluminum-indium-zinc-tin oxide (a-AIZTO), amorphous gallium-indium-zinc-tin oxide (a-GIZTO), yttrium-indium-zinc-tin oxide (YIZTO), lithium-indiumzinc-tin oxide (LIZTO), and magnesium-indium-zinc-tin oxide (MIZTO). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The most attractive application of MO TFTs is active-matrix backplanes for organic light-emitting diode (OLED) display due to their high mobility, high transparency in the visible region, and low-cost production with solution process. 17,18 A vacuum process, such as sputtering, plasmaenhanced chemical vapor deposition, and atomic layer deposition, needs high manufacturing cost for display application.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44] In a previous report, Gadoped IZTO TFT (350 C) using AlO x as a gate insulator exhibits the mobility of 11.80 cm 2 V À1 s À1 (V DS ¼ 0.1 V, and V GS ¼ 3 V). 10 H. Yang et al reported that Ga-doped ITZO TFT (350 C) exhibits mobility higher than 30 cm 2 V À1 s À1 (V DS ¼ 40 V, and V GS ¼ 20 V). Nomura et al reported the percolation conduction mechanism in multicomponent MO with heavy transition metal cations with (n À 1)d 10 ns 0 (n $ 5) electronic conguration.…”
Section: Introductionmentioning
confidence: 99%